Slow virologic control but strong immune and metabolic recovery with dolutegravir-anchored therapy in an HIV cohort in Ghana - Mark Appeaning; Edwin Magomere; Alberta Mawulawoe Abotsi; Nana Ama Yeboaa Amoako; Kirk Elorm Kouffie; Becky Ewurama Tetteh; Bridget Nana Darkoa Quist; Christèle Nguepou Tchopba; Gloria Akosua Ansa; Evelyn Yayra Bonney; Peter Kojo Quashie (Virology Journal)
Abstract Introduction The West African HIV/AIDS epidemic, historically driven by HIV-1 CRF02_AG, other recombinant forms and HIV-2, remains less researched for various preventive and therapeutic interventions. We established the WACCBIP long-term HIV Infection Cohort (WHICH Study) to investigate the dynamics of HIV epidemic in Ghana. This report evaluates viral load dynamics, immune responses, and organ-level metabolic changes following antiretroviral therapy (ART) initiation. Method We collected blood samples, medical, and demographic data from ART-naïve individuals at baseline and six months post-ART, and from ART-experienced individuals at a single time point. Participants, aged 10 years and above, were purposively enrolled from six health facilities. Laboratory analyses included viral load, CD4 and CD8 counts, co-infection screening (hepatitis B/C, syphilis), liver and kidney function tests, haemoglobin estimation, and HIV-1/2 typing. Chi-square and logistic regression analyses were used to assess associations between participant demographics and clinical data with uncontrolled viremia and immune recovery. Results A total of 426 participants were recruited, comprising 159 ART-naïve and 267 ART-experienced individuals, with a mean age of 41.5 years. Median ART duration for ART-experienced was greater than 5 years. Infections included HIV-1 (78.6%), HIV-2 (2.1%), and dual HIV-1&2 (19.2%). Common comorbidities were anaemia (54.9%), hepatitis B (9.5%), and hypertension (8.2%). Most participant (97.9%) were on dolutegravir-anchored regimen. Among ART-naïve individuals, median viral load decreased from log10 5.16 at baseline to log10 4.64 copies/mL after six months (p = 0.0156). Median viral load for the ART-experienced arm was log10 3.23 copies/mL. Median CD4 count increased from 290 cells/mm³ in ART-naïve participants to 504 cells/mm³ at six-months post-ART (p = 0.0003) and 581 cells/mm³ in ART-experienced participants (p < 0.0001). ART-naïve participants were 19 times more likely to have unsuppressed viral loads at baseline compared to ART-experienced participants. ARTnaïve- participants had significantly decreased odds of immune recovery (aOR = 0.35, 95% CI: 0.140–0.85, p = 0.021), as did those with low CD4/CD8 ratio (aOR = 0.06, 95% CI: 0.02–0.20; p < 0.001). Kidney function and haemoglobin levels were significantly improved six-month post-ART among the ART-naïve group. Conclusion This study highlights the significant reduction in viral load and improved immune recovery following ART initiation despite uncontrolled viremia in a subset of participants. This cohort presents an opportunity to study Ghana’s local HIV epidemic, including HIV-1 and HIV-2, and impact of ART on disease progression.